Punishment of Theft in Islam and Its Enforcement In Pakistan - Ullah, Muhammad Ikram; Haq, Sami ul; Rehman, Badshah (Journal of Islamic and Religious Studies, 2020)
The Shari’ah classifies punishments into Ḥudūd, Qiṣāṣ, and Ta’zīr which aim to protect life, lineage, reason, property, and intellect in order to provide welfare and protection to the society. The Islamic system of punishments described different punishments on committing different crimes, i.e; murder, theft, adultery, intoxicant, blasphemy, and robbery, etc. The study concludes that in respect of Ḥudūd and Qiṣāṣ the power of the court is limited but in Ta’zīr punishments the court has wider power. The punishments that are described in PPC are not similar to punishments mentioned in Qur’ān. The Federal Shari’ah Court has supported the punishment of amputation of the hand against the crime of theft which is similar to the punishment of Qur’ān. Ḥadd punishment of theft in Pakistan is not implemented because the conditions i.e. at least two Muslim adult males eye-witnesses and Tazkiyah al-Shuhood (truthful person and abstain from major sins) are very difficult to fulfill to the extent that Shariah demands. Therefore theft in Pakistan is punishable with Ta’zīr punishment.